2001
DOI: 10.4049/jimmunol.166.3.1492
|View full text |Cite
|
Sign up to set email alerts
|

The Human Endoplasmic Reticulum Molecular Chaperone BiP Is an Autoantigen for Rheumatoid Arthritis and Prevents the Induction of Experimental Arthritis

Abstract: Rheumatoid arthritis (RA) is the most common, crippling human autoimmune disease. Using Western blotting and tandem mass spectroscopy, we have identified the endoplasmic reticulum chaperone BiP, a 78-kDa glucose-regulated protein, as a possible autoantigen. It preferentially stimulated increased proliferation of synovial T cells from patients with RA but not from patients with other arthritides. Mice with established collagen- or pristane-induced arthritis developed IgG Abs to BiP. Although BiP injected in CFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
137
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 47 publications
8
137
0
1
Order By: Relevance
“…Previously, we and other investigators have identified the immunoglobulin binding protein, BiP, alternatively known as glucose-regulated protein 78, as a putative autoantigen in RA (11,12). BiP is an endoplasmic reticulum chaperone and stress protein belonging to the Hsp70 family.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, we and other investigators have identified the immunoglobulin binding protein, BiP, alternatively known as glucose-regulated protein 78, as a putative autoantigen in RA (11,12). BiP is an endoplasmic reticulum chaperone and stress protein belonging to the Hsp70 family.…”
mentioning
confidence: 97%
“…BiP is an endoplasmic reticulum chaperone and stress protein belonging to the Hsp70 family. We previously demonstrated that patients with RA have anti-BiP antibodies in their serum (11). In addition, mice with CIA or pristane-induced arthritis produce anti-BiP antibodies.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The most prevalent autoantibody reactivity in RA is RF, with IgG-RF being particularly implicated in the formation of small immune complexes (2,22), but a significant proportion of patients also have raised levels of antibodies to cyclic citrullinated peptides (anti-CCP) (23) and to proteins such as the immunoglobulin heavy-chain binding protein (anti-BiP) (24). In the absence of T cell responses to IgG, there is particular interest in the possible roles of T cell responses to these other antigens and their interrelationships with RF B cells.…”
mentioning
confidence: 99%
“…Thus HSPA1 is well recognised as a proinflammatory ligand causing activation of human and murine monocytes [25]. In contrast, HSPA5, which has 64% sequence identity to HSPA1, is a potent monocyte inhibitor and anti-inflammatory protein which is starting trials as a therapy for the chronic inflammatory disease, rheumatoid arthritis [26,27]. Mycobacterium tuberculosis is one of a proportion of bacteria that have more than one gene coding for chaperonin 60 proteins and in this organism the proteins are termed chaperonin 60.1 and 60.2 (Hsp65).…”
Section: Molecular Chaperone Sequence Conservation and Biological Funmentioning
confidence: 99%